Initial experience in the extraction of chronically implanted pacemaker leads using the Excimer laser sheath. Issue 1 (1st July 1999) - Levy, T; Walker, S; Paul, V
Abstract : OBJECTIVE: To assess the safety and efficiency of the Excimer laser sheath in extracting chronically implanted pacemaker leads. PATIENTS: Eight patients were studied (one female, mean age 62 years, range 34 to 77) with 17 pacemaker leads (five atrial, 10 ventricular, two implantable defibrillator). The mean implantation time was 65 months (range 23 to 188). The indications for lead extraction were chronic infection (7), superior vena cava obstruction (4), lead malfunction (4), and pain (2). METHODS: A prospective analysis of the use of the Excimer laser sheath in extracting chronically implanted pacemaker leads. Laser sheath extraction was undertaken if conventional extraction techniques with simple traction or traction with a locking stylet had failed. If laser sheath extraction was unsuccessful, basket retrieval of the lead from the groin was performed. RESULTS: Complete lead removal was achieved in 16 leads (94%). In one case the electrode tip was left behind without complication. Extraction was achieved with the laser sheath alone in 16 leads. Basket retrieval was required in one case after laser failure. There were no complications. CONCLUSIONS: The Excimer laser sheath appears to be an effective and safe technique for extracting chronically implanted pacemaker leads. It can be used in combination with the currently available techniques for successful lead extraction.